Motivational interviewing with offenders: engagement, rehabilitation, and reentry - Stinson, Jill D. (Applications of motivational interviewing, 2017)
A new approach -- The spirit of motivational interviewing -- The art of listening -- The art of interviewing -- Engaging: the relational foundation -- Engaging: the relationship in practice -- Focusing and preparing for change -- Focusing in practice -- Evoking: moving toward change -- Evoking in practice -- Developing a plan -- Resistance reexamined -- The rise of motivational interviewing -- Implementation and sustainability -- Considerations, cautions, and comments